2021
DOI: 10.1016/j.hrthm.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Atrial resting membrane potential confers sodium current sensitivity to propafenone, flecainide and dronedarone

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Further function analysis showed that cardiomyocytes of the left atria displayed a depolarized resting membrane potential and a smaller action potential amplitude than those from control mice [ 57 ]. However, an increase [ 60 ] and no change [ 56 , 62 ] in Scn5a expression were also observed in other studies. In addition to I Na and I K1 , remodelled I Ks and I CaL were associated with PITX2c overexpression in right atrial myocytes [ 59 ].…”
Section: The Role Of Pitx2 In Cardiogenesis and Arrhythmogenesissupporting
confidence: 53%
“…Further function analysis showed that cardiomyocytes of the left atria displayed a depolarized resting membrane potential and a smaller action potential amplitude than those from control mice [ 57 ]. However, an increase [ 60 ] and no change [ 56 , 62 ] in Scn5a expression were also observed in other studies. In addition to I Na and I K1 , remodelled I Ks and I CaL were associated with PITX2c overexpression in right atrial myocytes [ 59 ].…”
Section: The Role Of Pitx2 In Cardiogenesis and Arrhythmogenesissupporting
confidence: 53%
“…Further function analysis showed that cardiomyocytes of the left atria displayed a depolarized resting membrane potential and a smaller action potential amplitude than those from control mice [20]. However, an increase [21] and no change [79,83] in Scn5a expression were also observed in other studies. In addition to INa and IK1, remodelled IKs and ICaL were associated with PITX2c overexpression in right atrial myocytes [23].…”
Section: Membrane Effector Genes Regulated By Pitx2mentioning
confidence: 51%
“…Bai et al and Syeda et al reported that the class I AAD flecainide was more effective in suppressing atrial arrhythmias in PITX2 v ariants than in the wild type ( 13 , 17 ). In contrast, Holmes et al reported that the class III AAD dronedarone offered a more prominent anti-AF effect than flecainide or propafenone in a murine PITX2 +/− heart model than in the wild type ( 10 ). In this study, we confirmed that class I AAD was more effective in PITX2 variants, consistent with the previous studies by Bai or Syeda ( 13 , 17 ).…”
Section: Discussionmentioning
confidence: 93%